Consumer Attitudes in the Context of the Concept of Planned Obsolescence - ÇERÇİ, MERVE; TOSUN, NURHAN ZEYNEP (MARMARA UNIV, FAC COMMUNICATION, 2021)
The concept of planned obsolescence refers to the systematic effort by the manufacturers to predetermine the usage period of consumer item. By planned obsolescence, manufacturers make sure that the product becomes unusable when the time allotted is over, encouraging individuals to purchase new consumer goods at certain intervals. Advertising is a crucial marketing communications effort to allow new purchases instead of products whose life curves have been deliberately shortened. This study aims to test the participants' tendencies towards planned obsolescence and measure the role of advertising in cognitive, emotional, and behavioral attitudes towards planned obsolescence. For this purpose, the participants were firstly divided into experimental and control groups. Afterwards, the participants in the experimental group watched Apple iPhone 8 and Apple New Year commercials, which were also used for manipulation. Whereas one of the commercials addresses the consumers' cognitive attitudes, the other one addresses consumers' emotional attitudes. By applying an experimental research design, this study included 586 validated questionnaires. As a result, when the commercials, addressing consumers' emotional and cognitive elements, attempted to manipulate the participants' attitudes, this research observed that the expected effects of this manipulation attempt did not occur and both groups displayed similar tendencies of planned obsolescence.
Keywords: Planned Obsolescence; Consumer Attitudes; Smartphone Users; Product Life Circle; Advertising